Synthesis and Biological Evaluation of Oxopyrido[2,3-d] Pyrimidine-7-ones Derivatives as Covalent L858R/T790M Mutant Selective Epidermal Growth Factor Receptor (EGFR) Inhibitors - Niu, Ao; Wang, Yang; Yang, Yushe; Wei, Jianhai; Ding, Jian; Chen, Yi; Tong, Linjiang; Xie, Hua (Letters in Drug Design & Discovery, 2019)
Background: None small cell cancer (NSCLC) is one of the most common cancer around the globe. First generation EGFR-TKI such as gefitinib and erlotinib are now documentated a prolonged PFS in NSCLC patients with EGFR activating mutation. However, upon continuous treatment, patients become resistant due toCEE T790M mutation in most cases.Second generation covalent EGFR inhibitors like afatinib have a moderate inhibition to EGFRT790M in preclinical models,but it is lacking efficacy in the clinical use for patients with T790M mutation due to the dose-limiting EGFRWT-driven toxicities.Third generation EGFR inhibitors have the potential to overcome EGFRT790M resistance mutations while reducing EGFRWT-driven toxicities and are now under active research. Methods: We took compound 6 as our lead compound. We focused on structural modifications around the hydrophile side chain, the linker, and the Micheal addition receptor moiety of AMG. A novel series of Oxopyrido[2,3-d]pyrimidine-7-ones derivatives have been designed and synthesized. Their kinase inhibition activity against EGFRWT and EGFRL858R/T790M were tested by ELISA assays. SRB test was used for cellular anti-proliferation evaluation. Results: A total of 21 novel Oxopyrido[2,3-d]pyrimidine-7-ones derivatives have been designed and synthesized. The compounds were characterized with 1H-NMR and HRMS. Their structureactivity relationships have been preliminaryly investigated. As a result, compound 7k showed comparable activity in kinase inhibition assay and cell growth inhibition assay with our lead compound 6. Higher activity and selectivity over EGFRWT were observed in the in vitro antitumour assay comparing compound 7k to AZD-9291. Compound 7a exhibited higher selectivity over EGFRWT in kinase inhibition assay, but poor cell inhibition to NCI-1975 cell line. The in vivo pharmacokinetic studies in rats showed that compound 9a exhibited improved pharmacokinetic profiles comparing to 6. Compound 9a was also efficacious in an NCI-H1975 murine xenograft model 30 mg/kg QD. Conclusion: Compound 9a has a potent kinase inhibition to EGFRT790M and has a high selectivity over EGFRWT. It’s also efficacious in an in vivo pharmacodynamic evaluation assay. Significant advantages were observed in pharmacokinetic evaluation comparing 9a to 6, which provide us a reference to further drug design and research.
Keywords: Non-small cell lung cancer